الشيخ أبو إسحاق إبراهيم إطفيش وجهوده الدعوية - سواكر, عبير; بن الشايب, مباركة; عطاء الله, نسرين; نصرات, وفاء (جامعة الوادي university of eloued, 2017)
في بحثنا هذا حاولنا جمع ماتفرق من اخبار الشيخ ابي اسحاق ابراهيم اطفيش ببعض فضله واشارة الى اهم جهوده الدعوية ابي اسحاق ابراهيم اطفيش عالم من اعلام الجزائر ،وواحد من اكبر علمائها واشهر دعاتها،ورمز من رموز الدعوة،وذالك بشهادة محبيه ولد الشيخ ابي اسحاق اطفيش سنة 5031 ه_ 5111 م بقرية بني يزقن )يسحن( بوادي ميزاب نشأ ابي اسحاق ابراهيم اسحاق اطفيش بحتوائه العائلة الكريمة بيت يقع بحي بحمان ،قابله المسجد العتيق وسط القمر بني يزقن وحرص والده ابي اسحاق على الغرس الوجان الديني في ابنه ،وتعليمه القيم الاسلامية وتلقينه علوم ذالك العصر ،فكانت نشأته العلمية متنوعة وكان اولها سنة 5180 م_ 5055 ه بدخوله كتاب الشيخ عمر بن احمد الز روالي وتمكن وهو ابن احدى عشر سنة ان يحفظ القران كريم على ظهر قلب،اخذ بعض مبادئ في علوم العربية . نشأ جمعية ادبية وكتابة في الصحف التونسية،وكتابة المقالات،ومشاركة في الحركات سياسية في البلاد التونسية. ملخص الدراسة Summary In this research, we tried to gather together some of the news of Sheikh Abi Ishaq Ibrahim Atfish with some of his virtue and a reference to his most important advocacy efforts Abi Ishaq Ibrahim Atefich is a world of the flags of Algeria, one of its greatest scientists and the most famous of its preachers, and a symbol of the symbols of the call, Shaykh Abi Ishaq Atfish was born in 1305 AH in 1888 in the village of Bani Yazqan (Yashn) in the valley of Mesab The father of Ishaq Ibrahim Ishaq Atefich grew up in the house of Bahamoun. He was met by the ancient mosque in the center of the moon, Bani Yazkan, and his father Abi Yazak was keen on planting the religious fowl in his son. He taught him Islamic values and taught him the sciences of this era. The first was the year 1893 AD. Omar bin Ahmed Zerouali and managed to be a son of eleven years to keep the Koran Karim on the back of the heart, taking some principles in the science of Arabic. A literary and writing society was established in Tunisian newspapers, writing articles and participating in political movements in the Tunisian country.
دعوة